Analysis Determinants of Consumer Purchase Interest to Imported Fashion Products on The Instagram Platform - Firda Sasmitha Dewi; Norman Arif; Ali Taman; Imron Hamzah (Profesional Muda Cendekia Publishing, 2021)
In this era of social media, more effort is needed to win consumer appeal, consumer interest is the goal of achieving sales. Therefore, it is necessary to have a strategy for the company to get consumer appeal. The purpose of this study was to analyze the factors that influence consumer attractiveness to imported clothes on social media, especially on Instagram. This study uses primary data through a questionnaire. The sample collection technique uses non-probability sampling with accidental sampling method. The samples obtained were 50 samples. This study uses multiple regression analysis methods using SPSS statistical tools. The empirical results show that partially the product variable and the variable price have no effect on the attractiveness of consumers on imported clothing, then the variable promotion has a significant effect on the attractiveness of consumers on imported clothing. In addition, simultaneously all the independent variables together have a significant positive effect on consumer attractiveness to imported clothing on Instagram.